KEWAJIBAN NAFKAH DALAM KELUARGA PERSPEKTIF HUSEIN MUHAMMAD - Wardah Nuroniyah; Ilham Bustomi; Ahmad Nurfadilah (Mahkamah : Jurnal Kajian Hukum Islam, 2019)
The obligation of living in the family or in the concept of fiqh that the obligation of living is borne by the husband, this is because the male leadership over women therefore the husband is charged with his wife's wages. But over time, the concept of living in fiqh now seems irrelevant. Not a few, it is the wife who plays a role in earning a living in the family. It is clear that the division of roles like this seems to cause inequality in the family. The obligation of living in the family according to KH Husein Muhammad is charged not to the husband, but who can afford him who is obliged. This means that it is not fixed on the husband. His thought that at that time, men were considered as public beings while the wives of domestic beings. In this position lasted for centuries. However, when in context, women are more capable, more productive and husbands make a living. So according to him there is no element of justice, while the husband is in a position of incapacity. This is what underlies his thinking regarding the obligation of living.